Legal Regulation of Transboundary Natural Resources - Altayeva, Kamilya Zh.; Yergobek, Shynggys K.; Mynbatyrova, Nurlaiym K.; Zhailau, Zhanat; Kuderin, Ilyas K.; Mashimbayeva, Gulmira A. (Journal of Environmental Accounting and Management, 2026)
The article examines aspects of the legal characterization and regulation of natural resources’ treatment that are jointly owned or geographically located in two or more states. It is shown that political, social, sociological and economic prerequisites impose on the principles of such cooperation. Until now, the problem of joint management and use of natural resources and products of their processing remains unresolved. The work clearly shows how the regulation of transboundary natural resources takes place, and what should be included in this concept. The novelty of the work is in an aspect that shapes the notion of the availability of natural resources in globalization and cross-border trade. As a legal nature, it is proposed to create interstate commissions, as well as concessions, as the basis for the development of natural resources’ joint use. In this work, the notion of natural resources has been expanded – to those authors include not only minerals in the traditional understanding of natural resources, but also general ecosystems. The leading direction in the development of the situation is interstate cooperation on the biosphere’s conservation.